Terrorism and counter-terrorism: impact of ambiguous and disputed definitions on fundamental human rights - Marsili, Marco (2019)
The role of terrorism in political discourse changed dramatically over the last fifty years, moving from ambiguity to the forefront of public policy and security concern. After the 9/11 attacks, terrorism has earned the news headlines, and has become a global security priority. Governments and the international community have enhanced measures to counter international and transnational terrorism, although there is no universally accepted definition of the term. The lack of an undisputed and legally binding definition of terrorism leaves significant room for free interpretation by policymakers. Governments are given what is essentially a carte blanche to develop programs and counter-terrorism initiatives that may lead, or have already led, to the development of policy that infringes on fundamental human rights. This thesis investigates the connection between terrorism and fundamental human rights. The question that guided this dissertation is the potential consequence of arbitrary and politicallydriven definitions of terrorism over counter-terrorism policy and fundamental human rights. The thesis moves from a historical framing of the concept of terrorism that changes with time. There are many definitions of the term, and there is no common definition with legal value. The current debate on terrorism is linked almost exclusively with non-state actors, which implies that state and terrorism have no linkage, even if there are evidences of these ties. The thesis scrutinizes the instrumentalization of terrorism, starting from an analysis of the concept based on three pillars: historical, theoretical-conceptual and legal (in the light of international law and human rights law). Then an empirical analysis based on these tools through the use of political and legal mechanisms to obtain a political output was conducted. To answer the starting question, the research moved from a historical-documentary analysis, then took into consideration the literature, and focused on how the states use the justification of the fight against international terrorism to restrict fundamental human rights. After the theoretical-conceptual and legal analysis, the research focuses on the legal aspects of the War on Terror and security policies. Large part of the empyrical research is dedicated to scrutinize the case of Turkey after the 2016 coup d'état attempt, to review some rulings of the European Courts, and to examine some prominent 'terrorist' organizations. While this topic presents a serious challenge, it does open much room for possible explorations of new fields of research without necessitating a fixed point of departure – or arrival. The thesis ends suggesting some future research directions.